PERBANDINGAN PENGGUNAAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) DENGAN MODEL SNOWBALL THROWING TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS VIII SMP N 1 SUNGAI BEREMAS - Nuzul Nuzul (STKIP PGRI Sumatera Barat, 2021)
This research is motivated by the problem that students are still less skilled in writing poetry texts. This type of quantitative research with experimental models. The research sample was students VIII/40 SMP N1 Sungai Beremas (20/experiment 1 and 20/experiment 2). The research data was in the form of poetry text writing skill scores using the Numbered Head Together (NHT) model and the Snowball Throwing model for the eighth grade students of SMP N 1 Sungai Beremas. The results of this study can be considered as follows. First, the skill level of writing poetry text for VIII grade students of SMP N 1 Sungai Beremas using the Numbered Head Together (NHT) learning model obtained an average score of 60.83 with sufficient qualifications. Second, the skill level of writing poetry text of the eighth grade students of SMP N1 Sungai Beremas using the Snowball Throwing learning model with an average score of 70 with sufficient qualifications (LdC). Third, from the results of hypothesis testing that the alternative hypothesis (H1) is accepted at a significant level of 95% and dk = n1 + n2-2 because tcount> ttable (2.15> 1.66). In other words, there is a significant comparison between the use of the Numbered Head Together and Snowball Throwing learning models on the skills written by grade VIII students of SMP N1 Sungai Beremas.